1999
DOI: 10.1021/bi991321u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flap Modifications on Human FEN1 Cleavage

Abstract: The flap endonuclease, FEN1, plays a critical role in DNA replication and repair. Human FEN1 exhibits both a 5' to 3' exonucleolytic and a structure-specific endonucleolytic activity. On primer-template substrates containing an unannealed 5'-tail, or flap structure, FEN1 employs a unique mechanism to cleave at the point of annealing, releasing the 5'-tail intact. FEN1 appears to track along the full length of the flap from the 5'-end to the point of cleavage. Substrates containing structural modifications to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 40 publications
(122 reference statements)
3
73
0
Order By: Relevance
“…However, some differences in the ratios of products generated by the wild type and mutants were observed, e.g., more of the 22-nt-long product is produced by the mutant nucleases when compared with the wild-type enzyme. In the latter case most of the radiolabeled products run as trimers or pentamers, whereas reactions catalyzed by the modified proteins produce predominantly endonucleolytic products (19,21, and 22 mers). The major cleavage product obtained with the 5Ј endlabeled 5OVH substrate arose from hydrolysis of the second base-paired nucleotide in the duplex region yielding a product 16 nt in length.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some differences in the ratios of products generated by the wild type and mutants were observed, e.g., more of the 22-nt-long product is produced by the mutant nucleases when compared with the wild-type enzyme. In the latter case most of the radiolabeled products run as trimers or pentamers, whereas reactions catalyzed by the modified proteins produce predominantly endonucleolytic products (19,21, and 22 mers). The major cleavage product obtained with the 5Ј endlabeled 5OVH substrate arose from hydrolysis of the second base-paired nucleotide in the duplex region yielding a product 16 nt in length.…”
Section: Resultsmentioning
confidence: 99%
“…Bambara and coworkers (21) found that FEN1 is able to process substrates containing bulky adducts (even branched DNA structures) in the 5Ј tail. Our laboratory reported that T5 5Ј nuclease is able to digest double-stranded closed-circular DNA under conditions that promote duplex melting (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model predominantly accepted for mammalian FEN1 proteins has long been the threading or tracking model, wherein the protein recognizes the free 5Ј-ssDNA tail and threads the ssDNA strand through the helical arch. Upon reaching the junction, the protein is hypothesized to cleave the appropriate scissile phosphate (62,66,67). Based on work with the 5Ј-3Ј exonuclease domain of Escherichia coli DNA polymerase I, Joyce and co-workers proposed that FEN1 proteins initially recognize or capture the two-way junction and then thread the helical arch with the ssDNA 5Ј-flap (40).…”
Section: The Addition Of Monovalent Salt Does Not Inhibit Hfen1-catalmentioning
confidence: 99%
“…FEN1 appears to track along the full length of the flap from the 5'-end to the point of cleavage. (Bornarth et al, 1999). Therefore, the investigation on the FEN-1 protein functions on CTG/CAG repeat DNA is crucial for understanding the mechanism of triplet repeat instability.…”
Section: Introductionmentioning
confidence: 99%